2011
DOI: 10.1016/j.gca.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of extracellular polymeric substances (Bacillus subtilis) by adsorption to and coprecipitation with Al forms

Abstract: Stabilization of extracellular polymeric substances (Bacillus subtilis) by adsorption to and coprecipitation with Al forms Mikutta, R.; Zang, U.; Chorover, J.; Haumaier, L.; Kalbitz, K. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
80
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 48 publications
5
80
0
4
Order By: Relevance
“…The SOM effect on aggregation has traditionally been attributed to the inner sphere complexes between the carboxyl groups and cations of the mineral structure by the ligand exchange mechanism (Chorover and Amistadi, 2001;Mikutta et al, 2011). Others types of organo-mineral interactions are also proposed: i) hydrophobic interactions; ii) C-O-alkyl groups and mineral hydroxyls; iii) cation bridges; iv) anion and cation exchange; and v) Van der Waals interactions (Stumm, 1992;Dick et al, 2009;Hanke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOM effect on aggregation has traditionally been attributed to the inner sphere complexes between the carboxyl groups and cations of the mineral structure by the ligand exchange mechanism (Chorover and Amistadi, 2001;Mikutta et al, 2011). Others types of organo-mineral interactions are also proposed: i) hydrophobic interactions; ii) C-O-alkyl groups and mineral hydroxyls; iii) cation bridges; iv) anion and cation exchange; and v) Van der Waals interactions (Stumm, 1992;Dick et al, 2009;Hanke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical models hold that hydrophilic groups, which are abundant in oxidizing environments, interact directly with the mineral surface; this occurs mainly with Fe and Al oxides, due to their high density of monocoordinated hydroxyls (Krull et al, 2003;Schöning et al, 2005;Wiseman and Püttmann, 2006;Mikutta et al, 2011). Some studies have indicated that in aerobic soils, the surface of Fe oxides can interact directly with carbohydrate-like structures that are more labile compounds, and not only via ligand exchange with carboxyl groups (Miltner and Zech, 1998;Schöning et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, protons and organic acids released by plants, or produced during oxidation of plant litter, can lower soil pH, promote mineral dissolution, and increase the concentration of Al and iron (Fe) in soil solution (Binkley and Richter 1987;van Breemen et al 1983). Monomeric and colloidal Al and Fe can then react with biomolecules to form complexes that deter microbial degradation, facilitating retention of soil organic C and N Mikutta et al 2011;Scheel et al 2008). Degradation of soil organic substrates can also be inhibited at low soil pH due to toxicity of Al ions (Scheel et al 2008), reduced exoenzyme activity (Sinsabaugh et al 2008), or shifts in microbial community composition (Fierer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O pH do ponto de carga zero (pH PCZ) desses óxidos é elevado, com valores entre sete e nove; no pH normal de solos tropicais e subtropicais (4-7) há predomínio desses grupos em suas formas protonadas (-AlOH 2 +0,5 e -FeOH 2 +0,5 ) (Schwertmann e Taylor, 1989), que facilitam a adsorção de compostos orgânicos. A grande densidade de hidroxilas monocoordenadas na superfície dos óxidos de Fe, como hematita (Hm) e goethita (Gt), pode levar à formação de interações fortes, como complexos de esfera interna, entre os grupos orgânicos e os minerais (Schwertmann e Taylor, 1989;Omoike e Chorover, 2006;Mikutta et al, 2011).…”
Section: Introductionunclassified
“…Mudanças no estádio de oxidação do metal, ocasionadas pela transferência de elétrons pelo ligante durante a formação do complexo, também podem influenciar o processo de dissolução, por meio da alteração do raio iônico do metal. Durante a formação do cristal, a formação de complexos pode ainda inibir ou retardar o crescimento de determinado plano cristalográfico (Omoike e Chorover, 2006;Mikutta et al, 2011;Henneberry et al, 2012).…”
Section: Introductionunclassified